Ikhanda : an ethno-historical archaeological investigation of Nguni military homesteads between the Mfolozi and Tugela Rivers, Kwa-Zulu Natal, South Africa - Pikirayi, Innocent (University of Pretoria, 2015)
Dissertation (MA)--University of Pretoria,2015.